The Romanian Migrant Communities of Italy. A Case Study in Ostiglia, Lombardy - Mihai Pascaru; Andreea Elena Nicoara (European Scientific Journal, ESJ, 2016)
The theoretical foundation of the current study consists in the distinction between community and society proposed by Ferdinand Tönnies in a famous 1887 book. Building upon this foundation and upon the results of a qualitative research survey of the Romanian migrants in the city of Ostiglia, Italy, the study will attempt sketching some answers to the following questions: 1) Do Romanian migrants constitute a particular community where they work?; 2) What is the role of the Church in the structure of the community life?; 3) What role do leisure time activities play in the consolidation of the community life?; 4) What role can the constitution of a real community have in its members' decisions to remain abroad on a permanent basis? The data was collected through a series of semi-structured interviews. We found that the Romanian migrants from Ostiglia tend to congregate into a temporary community, their communal ties being enhanced by the existence of a Romanian church in the Italian city. Shared leisure time also fortifies intra-community ties. Nevertheless the community is not a critical factor in migrants' decision to leave or permanently remain in Ostiglia.